The radical programme (1885). [By] Joseph Chamberlain & others. With "The future of the radical party" By T.H.S. Excot.. Ed. with an introd. by D.A. Hamer (The Harvester Press, 1971)
Photomechanical reprint of the ed.: "The radical programme". N.pl., Chapman & Hall, 1885. "The future of the radical party". N.pl., The Fortnightly Review, 1883, July 1.